Structural investigations on arabinogalactan-proteins from a lycophyte and different monilophytes (ferns) in the evolutionary context. (15th September 2017) - Bartels, Desirée; Classen, Birgit
Highlights: This contribution provides the first detailed characterization of AGPs from a lycophyte and different monilophytes. Investigated AGPs share general structural features with AGPs from angiosperms like a protein with Hyp and type II AG moieties. A special feature of investigated fern AGPs but not Lycopodium AGP is the unusual monosaccharide 3-O-methyl-rhamnose. A unique attribute of Lycopodium AGP are high amounts of terminal pyranosidic arabinose residues. The study contributes to better understanding of evolution of AGPs and plant cell wall. Abstract: Today, understanding of cell wall evolution is incomplete due to limited knowledge of cell wall structure of non-flowering plants. Besides polysaccharides, proteoglycans like arabinogalactan-proteins are important constituents of the cell wall of most if not all seed plants. This article provides the first detailed characterization of AGPs from a lycophyte and different ferns, which are the closest living relatives to seed plants. The amount of protein in fern AGPs (6–12%) was in a range comparable to most seed plant AGPs. However, it was higher for Lycopodium AGP (17%). The carbohydrate moieties of investigated AGPs showed typical features known for type-II arabinogalactans from seed plants and showed cross-reaction with polyclonal antibodies raised against Echinacea AGP. On the other hand, unusual structural components like high quantities of pyranosidic arabinose residues for Lycopodium AGP and 3- O -methyl-rhamnose for fern AGPs have been detected.